2022
DOI: 10.1021/acssuschemeng.2c03412
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Amidoximated Polyethylene Nanofibrous Membranes for Practical Uranium Extraction from Seawater

Abstract: As the key material of the adsorption method used for practical uranium extraction from seawater, the adsorbent should have a high uranium adsorption capacity and long service life. Polyethylene nanofibrous membranes (PENFMs) using a one-step grafting strategy to prepare scalable membrane adsorbents are reported with supreme uranium uptake capacity and long service life. A series of amidoximated polyethylene nanofibrous membrane (called amidoximated membrane or AM) adsorbent materials with different degrees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…[38,39] As per Figure 8b,e as well as Table S5 (Supporting Information), the peak of -NH 2 shifted from 401.18 to 401.38 eV, whereas that of -NH-changed from 399.18 to 399.38 eV, suggesting that the adsorption of U(VI) on PAGM-1 depends on-NH 2 and -NH-. [40,41] Furthermore, in the XPS spectrum of O 1s (Figure 8c,f as well as Table S5, Supporting Information), the binding energy of the oxygen-containing functional groups after the U(VI) adsorption shifted to a higher value. For example, COO − shifted from 530.78 to 530.88 eV, CO shifted from 531.68 to 531.98 eV, and C = O shifted from 532.78 to 532.88 eV.…”
Section: Adsorption Mechanism Of the Adsorbentmentioning
confidence: 96%
“…[38,39] As per Figure 8b,e as well as Table S5 (Supporting Information), the peak of -NH 2 shifted from 401.18 to 401.38 eV, whereas that of -NH-changed from 399.18 to 399.38 eV, suggesting that the adsorption of U(VI) on PAGM-1 depends on-NH 2 and -NH-. [40,41] Furthermore, in the XPS spectrum of O 1s (Figure 8c,f as well as Table S5, Supporting Information), the binding energy of the oxygen-containing functional groups after the U(VI) adsorption shifted to a higher value. For example, COO − shifted from 530.78 to 530.88 eV, CO shifted from 531.68 to 531.98 eV, and C = O shifted from 532.78 to 532.88 eV.…”
Section: Adsorption Mechanism Of the Adsorbentmentioning
confidence: 96%
“…80 Yu et al reported a novel one-step grafting approach to produce an expandable membrane-based sorbent to enhance the U recovery from both the simulated and natural seawater. 81 An array of amidoximated (AM) polyethylene nanofibrous membranes (PENFMs) were fabricated through one-step radiation-induced graft polymerization (RIGP) of acrylonitrile (AN) and acrylic acid (AA), followed by their amidoximation (Figure 3a). The synthesized membranes were thoroughly characterized by FT-IR, SEM, solid-state NMR, and XPS.…”
Section: Membranesmentioning
confidence: 99%
“…Graphene-based sorbents have gained increasing attention as promising materials for efficient and selective extraction of various ions from seawater. A hydrogenated form of graphene exhibits an excellent thermal and chemical stability, as well as a high surface area, making it an attractive candidate for sorption applications. Similar to the layered double hydroxides (LDHs), graphene-based sorbents possess interlayer spaces that allow efficient ion exchange, enabling the selective removal of contaminants from seawater. Recently, there has been a growing interest in using graphene oxide (GO) based materials/sorbents for the removal of U salts from seawater. , The GO-based nanocomposites (with large surface area) are highly functionalized materials and can be modified to incorporate different functional groups to expand their application.…”
Section: Inorganic Substrate-based Sorbents For Selective Uesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Nevertheless, UES is challenging due to the low uranium concentration (about 3.3 ppb). 4 Several extraction techniques, such as adsorption [5][6][7] flocculation, 8,9 membrane separation, [10][11][12] solvent extraction, 13,14 and ion exchange, 15,16 have been developed to extract uranium from seawater. Among the available methods, adsorption is deemed an efficient approach owing to its inherent cost-effectiveness, exceptional efficacy, and versatile potential for customization and operation.…”
Section: Introductionmentioning
confidence: 99%